Reyes, Esperanza. In the name of the State. Public servants in a health microgrid on the rural coast of Peru. Lima: Universidad Peruana Cayetano Heredia / Instituto de Estudios Peruanos / Global Health, 2007, 286 pp. - Anderson, Jeanine (2008)
The review does not present a summary